KAJIAN ANALISIS KEBIJAKAN STRATEGIS PENGELOLAAN PERUSAHAAN DAERAH DI PERUSAHAAN DAERAN BANK PERKREDITAN RAKYAT (BPR) KOTA MAKASSAR - M. Rustan DM; Mariah Mariah (Jurnal Bisnis dan Kewirausahaan, 2019)
Rural Banks are one of the conventional banks that carry out their business activities, among others 1) Collecting funds from the public in the form of deposits in the form of time deposits, savings deposits and / or other similar forms; 2) Providing Credit; 3) placing funds in the form of SBIs, time deposits, certificates of deposits and or savings with other banks. The results of this study provide information about how to formulate a strategic policy to encourage increased income for regional companies in the Makassar City Rural Bank and evaluate the implementation of strategic policies that have been implemented by the management of PD BPR Makassar City and Makassar City Government as owners of PD BPR. The results obtained from this study are that the main problem faced by the BPR of Makassar City at present is that the problem is actually quite long, namely the unavailability of sufficient working capital funds to support its business activities. So what and however the strategic policy taken by management is always stuck on the same classic problem. Poor past performance causes awarness (trust) of the community to be very low, so that the products launched are less attractive. The low level of competence, discipline, and performance of existing human resources so that they cannot or are less able to create attractive products, that is with the low level of services they have.